Croatia : Fiscal (De)centralization and Public Service Delivery - World Bank (Washington, DC, 2013)
This report discusses the contours of a possible strategic direction, the necessary basic institutional set up for implementation, and key reform policy options to be tackled in order to complete the foundations of the decentralization reform initiated in 2001. Croatia is still a highly centralized country in terms of decision making on public service financing and delivery, as compared to most of the new European Union members. One indicator is that the sub-national Government's budget still corresponds to five percent of GDP, while in the newly accessed countries it was about eight percent on average in their immediate pre-accession phase. The Government of Croatia is conscious about the critical importance of improving citizens' voice, transparency and accountability on public affairs, especially on matters of local interest, in order to increase efficiency on public service delivery and rapidly converge to European Union standards on a sustainable basis. The Government started its decentralization reforms in July 2001, although they have not yet adequately implemented them to make the reform process sustainable.